What’s the story here? The effect of volatility on university leader sensemaking of undocumented student access - Parrish, Dan (2020)
This paper examines the effects of volatility on sensemaking. While multiple studies have explored sensemaking in crisis situations, none have explicitly investigated the impact of volatility on organizational sensemaking. Interviews with 55 top leaders in U.S. Catholic universities reveal the effects of volatility on leader sensemaking of undocumented student access to their institutions. Under conditions of high volatility, leaders experienced a strong temptation to restrict communication, which is precisely the wrong thing to do since it reduces requisite variety. With less requisite variety, people miss more cues, which can lead to constrained sensemaking and premature simplification. Based on these findings, we can better understand the impact of volatility on organizational sensemaking and resulting consequences as sensemakers engage volatile issues.